2020
DOI: 10.1111/jmp.12501
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of 17DD attenuated yellow fever vaccine in howler monkeys (Alouatta spp.)

Abstract: Background Alouatta spp. are highly susceptible to yellow fever (YF) infection and develop an often fatal disease. The threat posed by an outbreak started in 2016 leads us to investigate vaccination as a potential tool in preventing YF in non‐human primates (NHP). Methods Susceptible howler monkeys were immunized with three different concentrations of the human Brazilian commercial YF17DD vaccine. Post‐vaccination viremia/RNAemia, immunogenicity, and safety were characterized. Results The vaccine did not produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…17DD viremia was assessed at Day 0 (pre-vaccination), Day 5 and Day 30 using qualitative real-time Polymerase Chain Reaction (in-house real-time PCR [rt-PCR] performed at the Flavivirus Laboratory of Instituto Oswaldo Cruz [LABFLA] Fiocruz) 23 in serum and urine samples and plaque-forming unit assay (PFU, log10 PFU/mL) in serum samples (performed at LATEV/Fiocruz). 24 Participants were classified as having 17DD viremia if any of the assays (rt-PCR serum and urine or PFU) performed at Day 5 resulted positive. All samples collected at Day 0 were negative for 17DD viremia.…”
Section: Methodsmentioning
confidence: 99%
“…17DD viremia was assessed at Day 0 (pre-vaccination), Day 5 and Day 30 using qualitative real-time Polymerase Chain Reaction (in-house real-time PCR [rt-PCR] performed at the Flavivirus Laboratory of Instituto Oswaldo Cruz [LABFLA] Fiocruz) 23 in serum and urine samples and plaque-forming unit assay (PFU, log10 PFU/mL) in serum samples (performed at LATEV/Fiocruz). 24 Participants were classified as having 17DD viremia if any of the assays (rt-PCR serum and urine or PFU) performed at Day 5 resulted positive. All samples collected at Day 0 were negative for 17DD viremia.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the actions aiming to control the impacts of yellow fever, an intensive investigative effort supported by the Committee for Management of Alouatta guariba is underway to verify if vaccination could be an effective tool for preventing the disease in Alouatta guariba. Preliminary results demonstrated that the 17DD attenuated yellow fever vaccine was safe and immunogenic for A. guariba (Fernandes et al, 2021). After that, other captive populations in Brazil are receiving the 17DD attenuated yellow fever vaccine, such as Centro de Pesquisas Bioloǵicas de Indaial and Instituto Espaco Silvestre (Santa Catarina); Centro de Manejo e Conservacão de Animais Silvestres and Instituto Libio (São Paulo) and Centro de Primatologia do Rio de Janeiro (Rio de Janeiro).…”
Section: Brazilmentioning
confidence: 99%
“…Howler monkeys are also especially susceptible to yellow fever virus and suffer high mortality within a few days of being bitten by the mosquitoes vectors (Rifakis et al, 2006;Fernandes et al, 2021). Thus, they play a key role as public health sentinels, providing early warning of the virus and allowing for increased vaccination of surrounding human populations.…”
Section: Introductionmentioning
confidence: 99%
“…YF virus detection at Day 5 and Day 30 was performed using qualitative real-time polymerase chain reaction (in-house real-time PCR [rt-PCR] at the Laboratory of Flavivirus (LABFLA/Fiocruz) [21]) in serum and urine samples; and plaque-forming unit (PFU) assay for quantification of viable YF viral particles (log 10 PFU/ ml) in serum (LATEV/Fiocruz) [22]. For analysis purposes, YF detection results were categorized as positive and negative.…”
Section: Yellow Fever Vaccine Safetymentioning
confidence: 99%